Unraveling the Fundamental Causes of Child Marriage in Lumajang Regency - Rohmadani, Eka Suci; Auliya Putri, Ananda Islami; Sari, Eka Ratna; Putri, Nabila Ananda; Nurseha, Faisol; Soegiono, Agie Nugroho (Universitas Sebelas Maret, 2025)
This study examines the underlying causes of the high rates of child marriage in Lumajang Regency, East Java. This study applies Giddens’ structuration theory to explore the dynamic interplay between economic, sociocultural, and educational factors. Using a qualitative approach, the research identifies three key factors driving early marriage practices: economic instability in families, sociocultural norms that legitimize early marriage, and limited access to and understanding of education and reproductive health. Economic factors include families’ inability to meet their needs, leading parents to marry their children as a temporary solution. Sociocultural norms, which still regard early marriage as part of tradition, exacerbate this situation. Finally, limited education and understanding of reproductive health make children more vulnerable to early marriage. In response, the Lumajang Regency Government issued Regulation No. 23 in 2020 to address this issue. However, the effectiveness of this policy is limited. This study recommends strengthening reproductive health education programs in schools, empowering economically vulnerable families, and enhancing the role of community leaders in disseminating the negative effects of child marriage to reduce early marriage rates.